Metformin and dietary advice to improve insulin sensitivity and promote gestational restriction of weight among pregnant women who are overweight or obese: the GRoW Randomised Trial. Issue 1 (December 2016) - Dodd, Jodie; Grivell, Rosalie; Deussen, Andrea; Dekker, Gustaaf; Louise, Jennie; Hague, William
Abstract Background Obesity is a significant global health problem, with approximately 50% of women entering pregnancy having a body mass index greater than or equal to 25 kg/m2 . Obesity during pregnancy is associated with a well-recognised increased risk of adverse health outcomes both for the woman and her infant. Currently available data from large scale randomised trials and systematic reviews highlight only modest effects of antenatal dietary and lifestyle interventions in limiting gestational weight gain, with little impact on clinically relevant pregnancy outcomes. Further information evaluating alternative strategies is required. The aims of this randomised controlled trial are to assess whether the use of metformin as an adjunct therapy to dietary and lifestyle advice for overweight and obese women during pregnancy is effective in improving maternal, fetal and infant health outcomes. Methods Design: Multicentre randomised, controlled trial. Inclusion Criteria: Women with a singleton, live gestation between 10+0 -20+0 weeks who are obese or overweight (defined as body mass index greater than or equal to 25 kg/m2 ), at the first antenatal visit. Trial Entry & Randomisation: Eligible, consenting women will be randomised between 10+0 and 20+0 weeks gestation using an online computer randomisation system, and randomisation schedule prepared by non-clinical research staff with balanced variable blocks. Stratification will be according to maternal BMI at trial entry, parity, and centre where planned to give birth. Treatment Schedules: Women randomised to theMetformin Group will receive a supply of 500 mg oral metformin tablets. Women randomised to thePlacebo Group will receive a supply of identical appearing and tasting placebo tablets. Women will be instructed to commence taking one tablet daily for a period of one week, increasing to a maximum of two tablets twice daily over four weeks and then continuing until birth. Women, clinicians, researchers and outcome assessors will be blinded to the allocated treatment group. All women will receive three face-to-face sessions (two with a research dietitian and one with a trained research assistant), and three telephone calls over the course of their pregnancy, in which they will be provided with dietary and lifestyle advice, and encouraged to make change utilising a SMART goals approach. Primary Study Outcome: infant birth weight >4000 grams. Sample Size: 524 women to detect a difference from 15.5% to 7.35% reduction in infants with birth weight >4000 grams (p  = 0.05, 80% power, two-tailed). Discussion This is a protocol for a randomised trial. The findings will contribute to the development of evidence based clinical practice guidelines. Trial registration Australian and New Zealand Clinical Trials RegistryACTRN12612001277831, prospectively registered 10th of December, 2012.